2016
DOI: 10.1039/c6nr03418g
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic changes in DNA conductance with stretching: structural polymorphism at a critical extension

Abstract: aIn order to interpret recent experimental studies of the dependence of conductance of ds-DNA as the DNA is pulled from the 3'end1-3'end2 ends, which find a sharp conductance jump for a very short (4.5%) stretching length, we carried out multiscale modeling to predict the conductance of dsDNA as it is mechanically stretched to promote various structural polymorphisms. We calculate the current along the stretched DNA using a combination of molecular dynamics simulations, non-equilibrium pulling simulations, qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 52 publications
7
62
0
Order By: Relevance
“…S14) with OS3 scheme (and melted-DNA with OS5 scheme) is independent of DNA length. It is worth mentioning that apart from the 12 bp and 30 bp length studied here, we have also looked at the force extension behavior for 20 bp long dsDNA in our recent work [78]. All these simulations prompted us to comment that the force-extension and H-bond breaking behavior is qualitatively insensitive to DNA length.…”
Section: E Effects Of Dna Length On the Emergence Of S-dnamentioning
confidence: 89%
“…S14) with OS3 scheme (and melted-DNA with OS5 scheme) is independent of DNA length. It is worth mentioning that apart from the 12 bp and 30 bp length studied here, we have also looked at the force extension behavior for 20 bp long dsDNA in our recent work [78]. All these simulations prompted us to comment that the force-extension and H-bond breaking behavior is qualitatively insensitive to DNA length.…”
Section: E Effects Of Dna Length On the Emergence Of S-dnamentioning
confidence: 89%
“…Experimental results of Albrecht et al show that the differences in behaviour of DNA when using different pulling schemes can depend on the loading rate, with stretching forces propagating first at high pulling rates, but shearing becoming dominant at slower pulling rates (Albrecht et al 2008). Others have also shown that there are structural differences when using different pulling mechanisms (Bag et al 2016; Danilowicz et al 2009; Roe & Chaka, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most readily available information on DNA under tension is the empirically measured force-extension curve (Rief et al 1999; Smith et al 1992), which provides the clear signal of some transition, but no atomistic-level information. This is supplemented by fluorescence and polarised-light studies (van Mameren et al 2009; Nordén et al 1992; King et al 2013), and by atomistic simulations which are able to provide explicit descriptions of the DNA but which are limited in the accessible timescales and system sizes (Bag et al 2016; Konrad & Bolonick., 1996; Lebrun & Lavery, 1996; Li & Gisler, 2009; Roe & Chaka, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…are variables as nuclear configuration evolves with time while the reorganization energy λ is pre-prepared parameter in our model. Refer to previous theoretical study, 16,23,26,31,41,42 their definitions and calculations are as follows.…”
Section: Ct Parametersmentioning
confidence: 99%
“…18 Renaud et al included the interactions with molecular vibrational modes in the Hamiltonian and obtained CT rates quantitatively consistent with experimental data. 17 On the other hand, a cross-scale method combining the MD, QM, Marcus electron transfer theory and kinetic Monte Carlo (MC) simulations was also employed to study DNA CT. 21,23 In comparison with the former, the latter is less used and needs more exploration.…”
Section: Introductionmentioning
confidence: 99%